DYNAMIC OF COMMUNITY: TERMS TA'ARUF BEFORE MARRIAGE PERSPECTIVE PROPHET'S HISTORY - Firdaus Chandra, Agus; Siam, Khusus; Nuryanti, Evi; Akmar, Khurratul (Universitas Islam Negeri Ar-Raniry, 2023)
This research is based on the fact that there are many prospective husband and wife pairs who do not carry out the ta'aruf process in accordance with religious law. Many of them violated several rules of the ta'aruf process itself. In addition, there are still many people who do not know and understand the meaning of ta'aruf and how the process is carried out during ta'aruf. Due to this lack of understanding, not a few parents and young people violate these rules, one of which is the interaction between men and women without a murobbi or intermediary from each potential partner. So that many young people who want to get a potential partner today are taking the wrong path, namely by dating. They mix up the term ta'aruf with dating on the grounds that they can get to know each other's personalities. It is very vulnerable to immoral acts. The purpose of this study is to find out more about how the ta'aruf process is and how the concept of ta'aruf is in the Prophet's Hadith. This research is a library research, namely by collecting, reading and reviewing various materials from several sources related to the problems studied. The source on which this research is based is from the Hadith of the Prophet, wherein the Hadith refers to the procedures that must be carried out in the process of ta'aruf. This article discusses the study of family law in Islam, more specifically regarding ta'aruf according to the perspective of the hadith of the Prophet Muhammad SAW. Family law is the law that regulates relations arising from family relationships. In the discussion it is stated that ta'aruf is one of the processes recommended by the Prophet before establishing a family relationship (marriage). Ta'aruf itself means to know more closely, in the sense that it is not just a name but also related to the vision and mission of the marriage of the prospective partner. This is the goal so that the family relationship that is lived can become a family that is sakinah, mawadah, warahmah.